No Tissue Expression of KRAS or BRAF Mutations in 61 Adult Patients Treated for Esophageal Atresia in Early Childhood - Dang, Kien Xuan; Ho, Tho; Sistonen, Saara; Koivusalo, Antti; Pakarinen, Mikko; Rintala, Risto; Stenman, Ulf-Hakan; Orpana, Arto; Stenman, Jakob (European Journal of Pediatric Surgery, 2018)
Background Previous studies have reported an association among esophageal atresia (EA), Barrett's esophagus, and esophageal adenocarcinoma later in life.Objective The objective of the article is to evaluate KRAS and BRAF mutations as potential genetic markers for early detection of malignant transformation, we used an ultrasensitive technique to detect tissue expression of KRAS and BRAF mutations in endoscopic biopsies from 61 adult patients under follow-up after treatment for EA.Materials and Methods RNA was extracted from 112 fresh-frozen endoscopic tissue biopsies from 61 adult patients treated for EA in early childhood. RNA was reverse transcribed using the extendable blocking probe reverse transcription method. KRAS codons 12 and 13, as well as BRAF mutations were detected by quantitative polymerase chain reaction.Results No mutations of KRAS codon 12, KRAS codon 13, or BRAF were found in 112 endoscopic biopsy samples from 61 patients.Conclusion Despite the presence of histological findings indicating long-standing gastroesophageal reflux in 25%, as well as symptomatic gastroesophageal reflux in more than 40%, there was no detectable tissue expression of KRAS or BRAF mutations in this cohort of patients.
Keywords: esophageal atresia; extendable blocking probe; KRAS; BRAF